A clash of priority between work and home: an experience of female professionals in a modernised Malaysia - Rokis, Rohaiza (Institut Sosial Malaysia, 2009)
This article explores the paradoxes relating to the intricate relationships of women, work and home in Malaysia. In general, employment activity enhances women;s economic independence and influences their negotiations about the divisions of labour in the home. But in Malaysia, the situation concerns the issue over conflicts of priorities, which seems to challenge the traditional gender roles of woman, wife, mother and homemaker. What happens when family commitments come into conflict with the demands of employment? when the two seems incompatible, which one gets priority? The research proposition rests on the stance that traditional and normative values still confine female professionals in Malaysia to set the priority for family work more than professional work despite modernisation. This article therefore attempts to identify their priority when the private-traditional sphere collides with the public-modernised sphere. It is derived from an in-depth structured interview method on 34 female professionals such as engineers, chemist and geologists who work at one petrochemical company in Malaysia, as well as higher-ranking ministerial personnel and human resource managers. The study found that even though female professionals enjoy their work, they still consider family and home as the priority in life. Modernisation has not able to change women's traditional attitude towards home commitment. Though they may be modernised, educated and professional, when it collides with home affairs, these women are still traditional at heart.